Gait Silhouette Enhancement with Modified CLAHE and Precise Gait Recognition Using a Lightweight Convolutional Neural Network - P., Nithyakani; Ukrit, Ferni (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Gait recognition is a behavioural biometric that can recognize an individual from a distance based on their walking pattern. Gait recognition techniques are persistently evolving for security purposes, as new advances in person recognition, range from traditional machine learning to deep learning. Various circumstances, such as lighting conditions, wearing garments, carrying a bag, and walking surfaces, can affect gait recognition performance. Furthermore, gait recognition from different points of view is a big challenge. A new framework, GRLNet: Light-weight Convolution Neural Network for Gait Recognition is proposed to identify the individual in various lighting conditions, clothing, etc. GRLNet is a portable architecture with a reduced memory size. Depth-wise and point-wise separable convolution is used to reduce the floating–point operations (FLOPs) and several parameters. A novel Hamming Correlated Gait Cycle Detection and Modified Contrast Limited Adaptive Histogram Equalization (MCLAHE) for gait silhouette image is proposed to enhance the gait energy image. Experiments on the popular public benchmark CASIA-B dataset was done to evaluate the efficiency of our proposed framework and our approach outperformed state-of-the-art solutions with covariates of carrying bag and wearing different clothes.